2009
DOI: 10.1007/s11689-009-9028-5
|View full text |Cite
|
Sign up to set email alerts
|

Autistic behavior in boys with fragile X syndrome: social approach and HPA-axis dysfunction

Abstract: The primary goal of this study was to examine environmental and neuroendocrine factors that convey increased risk for elevated autistic behavior in boys with Fragile X syndrome (FXS). This study involves three related analyses: (1) examination of multiple dimensions of social approach behaviors and how they vary over time, (2) investigation of mean levels and modulation of salivary cortisol levels in response to social interaction, and (3) examination of the relationship of social approach and autistic behavio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
58
1
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

5
2

Authors

Journals

citations
Cited by 50 publications
(69 citation statements)
references
References 55 publications
9
58
1
1
Order By: Relevance
“…Furthermore, the relationship between salivary cortisol and social approach behaviour during naturalistic social interactions has been explored in one study (Roberts et al, 2009). The method involved investigating social approach behaviour (physical approach, facial expressions and eye contact) with an experimenter when they were both unfamiliar (first minute of interaction) and familiar (during last hour of daylong assessment) to the child.…”
Section: Between-group Comparisons Of Cortisol Secretion In Humansmentioning
confidence: 99%
See 3 more Smart Citations
“…Furthermore, the relationship between salivary cortisol and social approach behaviour during naturalistic social interactions has been explored in one study (Roberts et al, 2009). The method involved investigating social approach behaviour (physical approach, facial expressions and eye contact) with an experimenter when they were both unfamiliar (first minute of interaction) and familiar (during last hour of daylong assessment) to the child.…”
Section: Between-group Comparisons Of Cortisol Secretion In Humansmentioning
confidence: 99%
“…In mice, no robust differences in baseline cortisol levels were seen, though there was some evidence of elevated stress-related reactivity. In human studies, baseline differences were observed in several studies (Hessl et al 2002;Roberts et al, 2009), as well as some indications of reactivity differences, compared to TD children Hessl et al, 2002;Roberts et al, 2009), though such differences may be mediated by gender and degree of autism symptomatology. At present, specific conclusions about the role of cortisol levels in behaviour associated with FXS are difficult to draw due to the high levels of variability and lack of correspondence between studies.…”
Section: Synthesis and Future Researchmentioning
confidence: 99%
See 2 more Smart Citations
“…A presença da FMRP no córtex motor já foi descrita anteriormente e é condizente com sinais apresentados pelos animais KO e pacientes afetados pelas síndromes relacionadas a FMRP, SXF e FXTAS, que mostram a habilidade motora diminuída na ausência da FMRP. Pacientes com a SXF exibem comportamentos estereotipados típicos do autismo, assim como atraso no desenvolvimento do controle motor fino (LARGO; SCHINZEL, 1985;ROBERTS et al, 2009;ZINGEREVICH et al, 2009). Estes sintomas motores começam a se apresentar na infância (BARANEK et al, 2008).…”
Section: A Fmrp E O Córtex Cerebralunclassified